2014
DOI: 10.1038/mt.2013.277
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Proof of Concept of Adoptive Immunotherapy for Hepatocellular Carcinoma Using Allogeneic Suicide Gene-modified Killer Cells

Abstract: Cell therapy based on alloreactivity has completed clinical proof of concept against hematological malignancies. However, the efficacy of alloreactivity as a therapeutic approach to treat solid tumors is unknown. Using cell culture and animal models, we aimed to investigate the efficacy and safety of allogeneic suicide gene-modified killer cells as a cell-based therapy for hepatocellular carcinoma (HCC), for which treatment options are limited. Allogeneic killer cells from healthy donors were isolated, expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Similarly to liver lymphocytes 8 , peripheral blood mononuclear cells (PBMCs) subjected to CD3+IL-2 activation present an IFN-γmediated antiviral activity toward HCV and an antitumor activity toward hepatocellular carcinoma, both provided mostly by CD56+ cells, including CD3 − CD56+ NKs and CD3+ CD56+ NK-like T cells. 21 These studies are consistent with our present results and with our recent report, demonstrating that high concentrations of SGMLs provided NK and NK-like T-cell-mediated antitumor effects in an hepatocellular carcinoma model 22 . However, as they were generated after short-term (3 days) activation with IL-2, this raises the question of the similitude of such activated lymphocytes, as well as of our SGMLs, with lymphokine-activated killer (LAK) cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly to liver lymphocytes 8 , peripheral blood mononuclear cells (PBMCs) subjected to CD3+IL-2 activation present an IFN-γmediated antiviral activity toward HCV and an antitumor activity toward hepatocellular carcinoma, both provided mostly by CD56+ cells, including CD3 − CD56+ NKs and CD3+ CD56+ NK-like T cells. 21 These studies are consistent with our present results and with our recent report, demonstrating that high concentrations of SGMLs provided NK and NK-like T-cell-mediated antitumor effects in an hepatocellular carcinoma model 22 . However, as they were generated after short-term (3 days) activation with IL-2, this raises the question of the similitude of such activated lymphocytes, as well as of our SGMLs, with lymphokine-activated killer (LAK) cells.…”
Section: Discussionsupporting
confidence: 93%
“…Using a humanized hepatocellular carcinoma mouse model, we previously demonstrated that, when infused intravenously, SGMLs preferentially homed to the liver and weakly migrated to the lungs. 22 This property is of advantage to improve the efficacy while limiting the peripheral spreading of SGMLs. Indeed, infusing SGMLs could allow reaching high local concentrations of IFN-γ, close to the target cells while leading to low peripheral IFN-γ concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and colleagues (23) infused a similar cell product in patients with HCC after ablation or surgical resection; the median time of recurrence-free survival was 44 months in patients receiving lymphocyte infusions and 30 months in the control group. Preclinical studies in vitro and in animal models suggest that much of the antitumor activity in such cell products is mediated by NK cells (36,37). Based on our results, the antitumor potential of expanded NK cells, particularly when armed with NKG2D-CD3z-DAP10 receptors, should be much higher than that of cytokine-activated lymphocytes.…”
Section: Discussionmentioning
confidence: 89%
“…These findings indicated that blocking STAT3 in HCC cells could initiate innate immunity in vivo . In a panel of HCC cell lines, human allogeneic suicide gene‐modified killer cells showed an IL‐2‐dependent, and non‐MHC class I‐restricted cytotoxicity in vitro and in vivo , mainly mediated by NK and NK‐like T cells …”
Section: Immunotherapeutic Strategiesmentioning
confidence: 92%